2013
DOI: 10.1007/s10195-013-0273-8
|View full text |Cite
|
Sign up to set email alerts
|

Proximal fractures of the humerus in patients older than 75 years of age: should we consider operative treatment?

Abstract: BackgroundOver 75 % of patients presenting with a proximal humerus fracture are 70 years or older. Very little is known about the outcome after operative treatment of these fractures in very old patients. This study was performed to gain more insight in safety and functional outcome of surgical treatment of proximal humerus fractures in the elderly.Materials and methodsIn this observational study, we analyzed all operatively treated patients, aged 75 or older, with a proximal humerus fracture between January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The results of screening and application of inclusion/exclusion criteria are outlined in Figure 1 . 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 …”
Section: Resultsmentioning
confidence: 99%
“…The results of screening and application of inclusion/exclusion criteria are outlined in Figure 1 . 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 …”
Section: Resultsmentioning
confidence: 99%
“…It is still controversial which treatment might be more appropriate, however a recent systematic review showed that conservative treatment is associated to lower complications while assuring good functional outcomes compared with surgery. 7 However, the observation that most of the single center cohort studies reported good outcomes [8][9][10][11] suggested that surgeon experience act in determining the results. Moreover, Boesmueller et al observed that the results of surgically treated PHF were related not only to patient's factors (age and smoking habits) but also to the quality of reduction.…”
Section: Introductionmentioning
confidence: 99%
“…While many orthopaedic surgeons may prefer surgical management in younger patients with displaced fractures of greater severity, a lack of consensus exists in older patients. 7 This controversy is only heightened in the elderly, with poorer bone quality 8 and increased risk for surgical intervention 9 and complication. It has been shown that these fractures are more prevalent in fit, independent patients, who function at a moderate level despite advanced age.…”
Section: Introductionmentioning
confidence: 99%